46. Skin DVHs predict cutaneous toxicity in head and neck cancer patients treated with radiochemotherapy. (December 2018) - Cattaneo, G.M.; Mori, M.; Dell'Oca, I.; Foti, S.; Calandrino, R.; Muzio, N. Di; Fiorino, C.
Abstract : Purpose/objective: To explore the association between planning skin dose-volume data and acute cutaneous toxicity after Radio-chemotherapy for Head and Neck (HN) cancer patients. Material/methods: Thirty-two HN consecutive patients were treated with Helical Tomotherapy (HT) with radical intent (SIB technique: 54/66Gy to PTV1/PTV2 in 30 fr) and neo-adjuvant or concomitant chemotherapy (no Cetuximab). A superficial body layer 2mm thick (SL2) was automatically delineated with a cranial-caudal extension corresponding to the high-dose PTV2 on planning CT. Prospectively evaluated CTCAE v4.0 acute skin toxicity information was available. Absolute dose-volume histograms (DVH) of SL2 were calculated and average values for patients who developed severe/moderate (G3/G2) and mild/none (G1/G0) skin acute toxicities were assessed. DVH differences were analyzed by two-tails t-test to define the most discriminative regions of SL2 DVH; dose-volume constraints were tentatively suggested. Results: The resulting average DVHs are shown in Fig. 1. Fifty-eight% of patients experienced G2/G3 toxicity (rate of G3: 27%) against 42% for G1/G0. Differences in skin DVHs were significant in the range 53–63Gy, suggesting that the fraction of SL2 receiving around 1.8-2 Gy/fr is highly correlated with the risk of skin acute toxicity: p-values ranged mostly between 0.005 and 0.01. Average V60 were 4cc and 11cc for the two groups and this parameter was highly discriminative (AUC:0.84, 95%CI: 0.64–0.95) with a best cut-off value equal to 3.3cc: the rate of G2/G3 toxicity was equal to 82% and 11% for V60 ⩾ 3.3 cc and < 3.3 cc respectively ( p = 0.003). Conclusion: Despite the limited number of patients, current results quantified for the first time the relationship between SL2 DVH and acute skin toxicity after HT of HN patients with a SIB approach. Additional research to corroborate this result on a larger group of patients is ongoing: if confirmed, these findings may support more effective skin-sparing planning strategies for HN patients.